Attack of the ninja frogs - Vernon, Ursula (New York : Dial Books for Young Readers, 2010)
When Suki the salamander--the new foreign exchange student--is being stalked by ninja frogs, Danny, Wendell the iguana, and Suki travel to Great-grandfather Dragonbreath's home in mythical Japan to find a solution for the problem.
Keywords: Amphibians -- Fiction; Dragons -- Fiction; Friendship -- Fiction; Ninja -- Fiction; Reptiles -- Fiction; Japan -- Fiction